PP.11.22: RATE OF GFR FALL OVER TIME, 24H AMBULATORY BP MONITORING AND OFFICE BP IN TRANSPLANT PATIENTS. (June 2015) - Mallamaci, F.; Porto, G.; Testa, A.; Tripepi, R.; Enia, G.; Leonardis, D.; Pisano, A.; Tripepi, G.; Zoccali, C.
Abstract : Objective: Current guidelines recommend 24hABPM as a priority for the diagnosis of hypertension and for treatment monitoring in pts likely to have a blunted nighttime BP decline and elevated CV risk, like renal transplant pts. Blunted nocturnal decline in BP is common in CKD and it is considered as the BP component with the strongest association with renal function loss over time in these pts. The relationship between 24 h ABPM components and the rate of GFR loss has never been investigated in these pts. Design and method: The rate of GFR loss was measured by fitting the slope of the GFR over time in series of at least 20 GFR measurements extended over 12 to 123 months. In 274 renal transplant pts with pre-planned, systematic 24hABPM measurement. 139 pts were excluded because they had insufficient repeated measurements of GFR over time. Thus, 135 pts were available for this analysis. Results: Baseline eGFR was 56 ± 21 ml/min/1.73 m2. The eGFR slope had a median value of 0.6 ml/min/year.On univariate analyses, eGFR slope was inversely related to office systolic BP (SBP), 24hSBP, night-time SBP and 24 h pulse pressure (PP) (all rho = -0.19, P = 0.03). EGFR slope was also inversely related to day-time PP (rho = -0.18, P = 0.04) and tended to correlate with day-time SBP (rho = -0.15, P = 0.08) and night-time PP (rho = -0.16, P = 0.07). The eGFR slope-BP components link become even stronger after adjustment for age, gender, smoking, diabetes, cholesterol and baseline eGFR: eGFR slope versus office SBP: beta = -0.25, P = 0.005; versus 24 h SBP: beta = -0.22, P = 0.01; versus night-time SBP: beta = -0.24, P = 0.007; versus 24 h PP: beta = -0.23, P = 0.01; versus day-time PP:beta = -0.21, P = 0.02; versus day-time SBP:beta = -0.18, P = 0.047; versus night-time PP:beta = -0.20, P = 0.03. Conclusions: When measured intensively and over extended time periods the rate of GFR loss in renal transplant pts associates with the BP burden. Even though measured at a single time point, office SBP associates with the GFR slope as strongly as 24 h SBP, day and night time SBP. These findings confirm the role of BP burden on long term evolution of renal function in renal transplant and indicates that it is unlikely that 24hABPM holds superior prognostic power for this outcome in this population.